PENGARUH BUDAYA ORGANISASI DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA PEGAWAI PDAM KABUPATEN KUDUS - Novi Permata Sari; Apriatni Endang Apriatni; Handoyo Djoko Waluyo (Universitas Diponegoro, 2014)
The purpose of this study was to determine the effect of organizational culture variables and physical work environment on employee performance PDAM Kabupaten Kudus . This type of research is explanatory research . In the study population there were 109 permanent employees and all PDAM Kabupaten Kudus were sampled by means of sampling or census saturated . Data were collected through questionnaires . Measurement scale using a Likertscale . Data analysis method used is correlation , simple and multiple linear regression with SPSS 20.0The study concluded that : ( a) organizational culture at PDAM Kabupaten Kudus strong ,as well as the physical work environment on PDAM Kabupaten Kudus Well ; ( b ) The effect of organizational culture on employee performance is strong at 0.805 ; influence of the physical work environment on employee performance is strong at 0.857 (d ) The results stimulatory or jointly demonstrate the organization's culture and physical work environment has a strong influence of 0.895 . Physical work environment variables have a greater influence than the culture of the organization.